2016
DOI: 10.3389/fped.2016.00024
|View full text |Cite
|
Sign up to set email alerts
|

Are Children Like Werewolves? Full Moon and Its Association with Sleep and Activity Behaviors in an International Sample of Children

Abstract: In order to verify if the full moon is associated with sleep and activity behaviors, we used a 12-country study providing 33,710 24-h accelerometer recordings of sleep and activity. The present observational, cross-sectional study included 5812 children ages 9–11 years from study sites that represented all inhabited continents and wide ranges of human development (Australia, Brazil, Canada, China, Colombia, Finland, India, Kenya, Portugal, South Africa, United Kingdom, and United States). Three moon phases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…While some studies have found minimal, or no association, between the moon cycle and sleep parameters 6,17,18 , they compared sleep during nights around the full moon to sleep during the nights of both the waxing/waning phases and the new moon. Our data clearly show these phases do not correspond to the peak and trough of sleep duration and onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have found minimal, or no association, between the moon cycle and sleep parameters 6,17,18 , they compared sleep during nights around the full moon to sleep during the nights of both the waxing/waning phases and the new moon. Our data clearly show these phases do not correspond to the peak and trough of sleep duration and onset.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the moon cycle, and more specifically moonlight associated with the 29.53-day long synodic month, can modulate human nocturnal activity and sleep remains a matter of controversy. Whereas some authors have argued against strong effects of moon phase on human behaviour and biological rhythms 5,6 , recent studies have reported that human sleep and cortical activity under strictly controlled laboratory conditions, which are absent from external temporal cues, are synchronized with lunar phases 7,8 .…”
mentioning
confidence: 99%
“…t is commonly believed that the full moon affects human behavior and the occurrence and outcome of various diseases. [1][2][3][4] Previous studies have suggested that lunar phases might be associated with an increased incident risk of cardiovascular diseases such as acute myocardial infarction (AMI) 3 or atrial fibrillation. 5 These cardiovascular diseases could be the cause of out-of-hospital cardiac arrest (OHCA).…”
mentioning
confidence: 99%
“…A recent article by Chaput and colleagues ( 1 ) provides evidence that if a relationship exists between lunar cycle and sleep duration and physical activity in children, its association is rather weak and less-than-meaningful. Using an international sample of 9- to 11-year olds ( n = 5812), monitored by accelerometers, Chaput and his team found no relationship between lunar cycle and physical activity, and a minimal effect between lunar cycle and sleep duration (~5 min/night less sleep under full moon vs. new moon).…”
mentioning
confidence: 99%
“…And in one of the few studies using children ( n = 795), Sjödin and colleagues ( 16 ) found longer sleep length and reduced activity, both occurring at the full moon phase. With respect to these works, the study by Chaput and colleagues ( 1 ) is the largest of its kind, in terms of sample size and geographic scope.…”
mentioning
confidence: 99%